Is Uganda on track in delivering on CEDAW recommendations - Aciro, Rita; Karayi, Laureen (Uganda Women’s Network, 2014)
This is an abridged report which highlights progress made and limitations that still persist relating to the promotion of women’s rights, gender equality and access to justice in Uganda. In 1985, Uganda ratified CEDAW, a global/ International Instrument to promote women’s rights. Ratification therefore means, Uganda has committed to fulfill its obligations under CEDAW including domestication of its legal and policy framework, periodic reporting to the CEDAW Committee and implementation of the Articles in CEDAW.